Przedstawiciele obcych narodowości w oczach Sienkiewicza podróżnika = Representatives of foreign nations as view ed through the eyes of Sienkiewicz the traveller - Kowalska, Danuta; Pietrzak, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article aims to present chosen portrayals of foreign nations and ethnic groups with which Sienkiewicz had contact during his journeys to America and Africa. The basis of this study is the account of travels, which took the form of a letter from journeys ("Portraits of America: Letters of Henry Sienkiewicz", "Letters from Africa"), popular in the second half of the nineteenth century.
Keywords: Sienkiewicz, Henryk (1846-1916); listy z podróży; punkt widzenia; stereotyp narodowy; letters from journeys; point of view; perspective; national stereotype